Modules To Improve Students' Higher Order Thinking Skills (Hots) On Human Reproductive System Materials - Windiyani Hasan; Elya Nusantari; Zuliyanto Zakaria (Cita konsultindo, 2026)
This study aimed to develop a Canva-based e-module that is valid, practical, and effective in improving students’ Higher Order Thinking Skills (HOTS) on the topic of the human reproductive system. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 35 eleventh-grade students of SMA Negeri 01 Gorontalo Utara. Data were collected through expert validation questionnaires (content experts, media experts, and practitioners), student practicality questionnaires, and HOTS pre-test and post-test. Data analysis was conducted using percentage calculations to determine validity and practicality, and the N-Gain test to measure effectiveness. The results showed that the e-module achieved a very valid category with an average score of 86%, a very practical category with a percentage of 92.77%, and was effective in improving students’ HOTS with an N-Gain score of 0.411, which falls into the moderate category. Therefore, the Canva-based e-module is feasible to be used as a biologi learning material to support the enhancement of students’ higher order thinking skills. learning.